Nanoencapsulation of liquid smoke/thymol combination in chitosan nanofibers to delay microbiological spoilage of sea bass (Dicentrarchus labrax) fillets - Ceylan, Zafer; Sengor, Gulgun F. Unal; Yilmaz, Mustafa Tahsin (ELSEVIER SCI LTD, 2018)
In this work, a combination of liquid smoke and thymol was encapsulated in chitosan nanofibers and the electrospun nanofibers were used to coat sea bass (Dicentrarchus labrax) fillets in order to delay growth of total mesophilic aerobic bacteria, psychrophilic bacteria and yeast and mold during storage period. The nanofibers were also characterized in terms of their zeta potential and fiber diameter values, microstructure and thermal decomposition. The dispersion stability (zeta potential) values were determined to range between 27.6 and 33.3 mV while fiber diameters were observed to differ from 72 to 132 nm. The electrospun nanofibers were in smooth, beadles, ultrafine, cylindrical and biopolymeric structure. The average weight loss in nanofibers were detected to be 85%. Microbiological stability tests demonstrated that the combination encapsulated in nanofibers was effective against growth of the tested microorganisms, exhibiting almost 60% limitation of growth in terms of total mesophilic bacteria. The coating of the fish fillets with the nanofibers encapsulated with the smoke/thymol combination would be a promising approach to delay microbial growth in fish fillets at cold storage conditions (6 +/- 1 degrees C). (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial surface-coating; Nanoscale material; Electrospun nanofiber; Microbial spoilage; Fish; EFFICACY; Engineering; Food Science & Technology